Local Employer Competition and Training of Workers - Sylvi Rzepka; Marcus Tamm (Institute for the Study of Labor (IZA), 2013)
The new training literature suggests that in a monopsonistic market employers will not only pay for firm-specific training but also for general training if the risk of poaching is limited. This implies that training participation should decrease when competition for employees is higher among firms. Using worker level data for Germany we find that the hypothesis is supported empirically. Specifically, we find that employees are significantly less likely to participate in training if the density of firms in a sector is higher within the local labor market.
Keywords: I24; J24; J42; 330; training; local labor markets; monopsony